Node Disjoint Random and Optimal Path Selection (NDROPS) Algorithm for Security in MANETS - P. Suma; O. Nagaraju; Md. Ali Hussain (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Mobile Adhoc Networks are shortly called MANETs. In these types of networks, fixed infrastructures are absent and are dynamic in nature. Nodes are movable, and they are not connected with any wires. For monitoring or supervising the transmissions in MANETS, no central supervision is present. Moving nodes, dynamic topology, and absence of infrastructure are the features of MANETs. These features are advantageous where wires cannot be used and where nodes are supposed to move. But there is a problem of security. Networks are highly prone to attacks where finding the root of the cause is very hard. Many nodes disjoint routing algorithms are proposed to balance the load, to cope up with link failures, etc. This paper proposes an algorithm called Node Disjoint Random and Optimal Path Selection (NDROPS) algorithm which uses the concept of dynamic routing and node disjoint routing to provide all the above-stated advantages along with security. Routing of data packets is done through few paths which are node disjoint. The main essence of this algorithm is to distribute the data among different routes. So, a malicious node in a path can retrieve only a few packets in random.  The simulation of the proposed NDROPS algorithm is performed and the performance is compared using throughout and packet drop probability.